Caspase-3/GSDME-mediated trophoblast pyroptosis and reciprocal macrophage polarization contribute to inflammation in early-onset preeclampsia - Huang, Baoying; Deng, Weinan; Bi, Shilei; Wang, Yifan; Tu, Zhaowei; Huang, Lijun; Du, Lili; Zhang, Lizi; Feng, Zhoushan; Sun, Wei; Liu, Tengfei; Kzhyshkowska, Julia; et al. (Advanced science, 2026)
Early-onset preeclampsia (EOPE) is associated with excessive apoptosis and inflammation, but the mechanistic link between these processes remains enigma. Here, we report elevated circulating pro-apoptotic proteins in EOPE patients at early pregnancy, along with concurrent CASP3 activation and GSDME cleavage in EOPE placentas. Using multiple trophoblast cell lines, we demonstrate that trophoblast cells, which highly express GSDME, undergo a shift from apoptosis to CASP3-dependent pyroptosis, driving inflammation. Notably, pyroptotic trophoblasts further induce pro-inflammatory macrophage polarization within placental villi organoids, establishing a feedback loop that amplifies both trophoblast pyroptosis and inflammatory responses in trophoblast organoids-macrophage assembloids. In vivo, CASP3-GSDME-mediated trophoblast pyroptosis contributes to systemic inflammation in wild-type pregnant mice but not in Gsdme−/− mice. Screening of EOPE prevention drugs reveals Vitamin D as a suppressor of GSDME activation and pyroptosis in trophoblast cells. Together, our findings establish CASP3-GSDME-mediated pyroptosis as a mechanistic link between apoptosis and inflammation in EOPE.